Characterization and Application of EST-SSR Markers Developed From the Transcriptome of Amentotaxus argotaenia (Taxaceae), a Relict Vulnerable Conifer - Ruan, Xiaoxian; Wang, Zhen; Wang, Ting; Su, Yingjuan (Frontiers in Genetics, 2019)
Amentotaxus argotaenia (Taxaceae) is a vulnerable coniferous species with preference for shade and moist environment. Accurate estimation of genetic variation is crucial for its conservation, especially in the context of global warming. In this study, we acquired a transcriptome from A. argotaenia leaves using Illumina sequencing, and de novo assembled 62896 unigenes, of which 5510 EST-SSRs were detected. Twenty-two polymorphic EST-SSRs were successfully developed and further used to investigate genetic variation, linkage disequilibrium, and bottleneck signatures of A. argotaenia. The results showed that A. argotaenia had moderate genetic variation and high genetic differentiation, which may provide raw material to be against climatic changes and accelerate local adaptation, respectively. No bottlenecks were found to occur in A. argotaenia. Our study not only showed that these EST markers are very effective in population genetic analysis, but also lay a solid foundation for further investigating adaptive evolution and conservation strategies of A. argotaenia.